MOTIVASI SANTRI PONDOK PESANTREN MUKHTAR SYAFA’AT DALAM MELANJUTKAN PENDIDIKAN DI IAI DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI - mahmudah mahmudah; Muhammad Imam Khaudli; Lubab Hakim (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2022)
The focus of this research is to find out the intrinsic motivation and extrinsic motivation in the students of the Mukhtar Syafa'at Islamic Boarding School in choosing to continue their education at IAI Darussalam. The approach in this study uses a qualitative approach, while the type of research uses descriptive research. The technique of determining the location uses a purposive area technique, while the technique of determining the research subject uses a purposive sampling technique. The results showed that the students who chose to continue their education at IAI Darussalam because they had intrinsic motivation in the form of a desire to develop themselves in continuing higher education. Meanwhile, extrinsic motivation is in the form of encouragement from the closest people, the need for a sense of security from the interference of the outside world, and because they can still stay at the pesantren to continue their early education at the pesantren.